Estratégias de aprendizagem para o ensino médio: construção de um recurso instrucional - Penso, Larissa Lazzeris (2024)
The aim of this research was to develop an instructional resource organized by areas of knowledge in order to promote the understanding and use of learning strategies among high school students. The study was based on a narrative literature review, which brought together scientific productions related to the application of these strategies in this context. Tos elect the articles, the Scientific Electronic Library Online (SciELO), Periódicos of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) and Periódicos Eletrônicos de Psicologia (PePSIC) data bases were consulted. The search included a combination of descriptors and Boolean operators, such as (―learning strategies‖ AND ―high school‖) OR (―learning methods‖ AND ―high school students‖) OR (―study techniques‖ AND ―adolescents‖ AND ―high school‖) NOT ―elementary school‖. After the review, the information obtained was systematized in a table to facilitate the analysis and interpretation of the data. Learning strategy sheets were drawn up based on concepts consolidated in the literature, as planned by Grehs (2020), Silva (2019) and Burochovitch et al. (2021). The sheets present the classification of the strategies (cognitive or metacognitive), a clear description of the behavior involved in using each strategy and an indication of the knowledge areas where they can be applied. This aims to enable students to apply them more effectively. The results indicated that all the research demonstrated in the context of secondary education revealed positive effects in the use of learning strategies. The instructional sheets' relevance is highlighted, as they provide conceptual information about the strategies and guide students in their application, identifying the areas of knowledge that can benefit the most from each one. It is hoped that the dissemination of the worksheets will enable secondary school teachers and students to use them as an effective tool for improving the teaching-learning process, promoting students' academic development and providing clear guidelines for the efficient application of learning strategies.